Pyrolysis of agricultural waste: effect of temperature and heating rate - Noor Hana , Md Yusof (2013)
Due to the depleting of non-renewable source energy (fossil fuel) and increases of environmental pollution, a search of sustainable alternative has gained significant attention. This involves the conversion of biomass from palm waste which are empty fruit bunch (EFB) and palm oil fiber (POF) to produce fuel gas, solid and bio-oil through pyrolysis. However the yield of products depends on some parameter. This research was carried out to study the effect of temperature and heating rate to the yield of products. The pyrolysis process was carried out using Quartz Glass Reactor in lab scale electrical tubular furnace. Preliminary analysis was conducted using thermo gravimetric analyzer (TGA) to determine the volatile matter and moisture content. From the result of TGA, it is found that POF contain more volatile matter in comparison of EFB. The CHNS analyzer also used to know the percentage of carbon, hydrogen, nitrogen and sulfur contained in the sample. The experiment was conducted to study the effect of temperature by varies the temperature to 400 oC, 500 oC, 600 oC and 700 oC and study the effect of heating rate by changing to 10 oC/min and 100 oC/min. The result showed that yield of bio-oil for both sample reaches maximum at 500 oC and decreases as the temperature increased. The yield of bio-oil increase from 55.7 wt% at 400 oC to 69.20 wt% 500 oC for EFB, while for POF the yield increase from 77.30 wt% at 400 oC to 89.10 wt% 500 oC For the fuel gas yield, the yield was seems to indirectly proportional with yield of bio-oil. When the yield of bio-oil increase the yield of fuel gas decreases and vice versa. For the solid yield, EFB and POF proved that yield of solid was decrease by the increases of temperature. It can be found that, the solid product produce 26 wt% and 65 wt% at 400 oC. Meanwhile, at 800 oC, only 10 wt% and 15 wt% solid product was found for EFB and POF. For study the effect of heating rate of EFB and POF, the result shows that yield of bio-oil high at high heating rate while the yield of fuel gas and solid was low at high heating rate. The highest bio-oil produced by both sample were 56 wt% and 89 wt%. The functional group and chemical compositions present in the bio-oil at optimum conditions were identified by using Gas chromatography Mass Spectrometry (GC-MS). From analysis, it is shown that bio-oil contains complex compound mostly from groups of phenol, alcohol, ketones, furans, and carboxylic acid